The efficacy of mobile phone-based text message interventions ('Happy Quit') for smoking cessation in China - Yanhui Liao; Qiuxia Wu; Jinsong Tang; Fengyu Zhang; Xuyi Wang; Chang Qi; Haoyu He; Jiang Long; Brian C Kelly; Joanna Cohen (BMC, 2016)
Abstract Background Considering the extreme shortage of smoking cessation services in China, and the acceptability, feasibility and efficacy of mobile phone-based text message interventions for quitting smoking in other countries, here we propose a study of "the efficacy of mobile phone-based text message interventions ('Happy Quit') for smoking cessation in China". The primary objective of this proposed project is to assess whether a program of widely accessed mobile phone-based text message interventions ('Happy Quit') will be effective at helping people in China who smoke, to quit. Based on the efficacy of previous studies in smoking cessation, we hypothesize that 'Happy Quit' will be an effective, feasible and affordable smoking cessation program in China. Methods/Design In this single-blind, randomized trial, undertaken in China, about 2000 smokers willing to make a quit attempt will be randomly allocated, using an independent telephone randomization system that includes a minimization algorithm balancing for sex (male, female), age (19-34 or >34 years), educational level (≤ or >12 years), and Fagerstrom score for nicotine addiction (≤5, >5), to 'Happy Quit', comprising motivational messages and behavioral-change support, or to a control group that receives text messages unrelated to quitting. Messages will be developed to be suitable for Chinese. A pilot study will be conducted before the intervention to modify the library of messages and interventions. The primary outcome will be self-reported continuous smoking abstinence. A secondary outcome will be point prevalence of abstinence. Abstinence will be assessed at six time points (4, 8, 12, 16, 20 and 24 weeks post-intervention). A third outcome will be reductions in number of cigarettes smoked per day. Discussion/Implications The results will provide valuable insights into bridging the gap between need and services received for smoking cessation interventions and tobacco use prevention in China. It will also serve as mHealth model for extending the public health significance of other interventions, such as mental health interventions. Trial registration NCT02693626 (Registration data April 11, 2016).